Orthodontic Treatment of Palatally Impacted Maxillary Canines with the Use of a Digitally Designed and 3D-Printed Metal Device - Georgios Vasoglou; Ioannis Lyros; Athanasia Patatou; Michail Vasoglou (MDPI AG, 2023)
The purpose of this article is to present a computer designed and 3D-printed metal device, which was used for the surgical exposure and orthodontic treatment of maxillary palatally impacted canines. In two cases which presented a palatally impacted canine, a Cone-Beam Computed Tomography (CBCT) was acquired and an intraoral scanning was performed, to determine the exact location of the canine. Based on a digital model, a device leaning on the teeth and mucosa was designed to serve as a guiding tool for the oral surgeon to expose the crown of the canine and help the orthodontist to provide proper traction. The device was then 3D-printed in biocompatible dental alloy and placed in the patients' mouth. After the surgical exposure of the canine's crown in both cases, a gold chain apparatus was bonded on and it was mounted on the metal projection of the device through an elastic chain. Within 3 months of traction, the crown of the canines appeared in the patients' palate to the exact location that was predicted and guided. A 3D-designed and manufactured metal device, with information acquired by CBCT and intraoral scanning, can be used for the exposure and traction of palatally impacted canines.